Building Digital and Sustainable Transportation of Indonesia Air Transport - Hadi Prayitno; Afen Sena; Putra Wicaksono (Journal of Information Technology, computer science and Electrical Engineering, 2024)
Air transportation as part of the national transportation system has an interest in building digital and sustainable transformation as part of the dynamics of public services which are directed towards world class services based on aspects of safety, capacity and efficiency, security, economic development and environmental protection. An implementation strategy approach that can be elaborated by capitalizing on software resources (infostructure & operation system transformation - transformation towards fulfilling compliance with ICAO SARPs, international best practices and domestic legislation/regulations), hardware (governance & portfolio transformation - transformation towards a sustainable public governance ecosystem both digitally) and brain ware (human capital transformation - human capital-based transformation) of the organization as well as optimizing the interface of science and technology and the related strategic environment in a directed, orderly and integrated manner through the 4 (four) "C" policy implementation method, namely Cooperation (stakeholder cooperation interests), Consensus (stakeholder agreement and agreement), Compliance (compliance with the implementation of laws, norms and ethics), and Commitment (firmness in carrying out planning, organizing, implementing and evaluating). With the belief that through the right and wise approach, the challenges of global priorities/strategic objectives as well as the dynamics of challenges in building digital and sustainable transformation of Indonesian air transportation can be controlled to realize safe, safe and comfortable Indonesian civil aviation.